2009
DOI: 10.1179/acb.2009.021
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement of Medicines in Belgium: Role of Evidence-Based Medicine

Abstract: The European Transparency Directive requires that pricing and reimbursement decisions must be taken in a transparent, objective and verifiable way with respect of strict timelines. The Belgian competent authority integrated on January 1st, 2002 Evidence-Based Medicine (EBM) principles in the reimbursement evaluation. The present work describes the procedures and investigates whether the introduction of the EBM principles indeed affects the decision and whether it compromised the respect of strict timelines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This effect was not observed in recommendations by National Institute of Health and Care Excellence (NICE) in the UK [17]. Van Wilder and Dupont showed that the percentage for positive decisions by the Minister was higher for class 1 drugs (70%) than for class 2 NME (64%) since the introduction of EBM principles in reimbursement decision in Belgium [23]. In this study, the advice of the CRM was considered.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This effect was not observed in recommendations by National Institute of Health and Care Excellence (NICE) in the UK [17]. Van Wilder and Dupont showed that the percentage for positive decisions by the Minister was higher for class 1 drugs (70%) than for class 2 NME (64%) since the introduction of EBM principles in reimbursement decision in Belgium [23]. In this study, the advice of the CRM was considered.…”
Section: Discussionmentioning
confidence: 77%
“…Decision making for reimbursement of drugs in general was previously analyzed in England, Wales, the Netherlands and to a limited extent in Belgium [17][18][19][20][21]23]. In the Netherlands, the type of disease for which a drug is indicated can influence reimbursement decision making since oncology drugs were more often recommended compared with drugs for other diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…The Belgian Commission on Reimbursement of Medicines (CRM), installed in January 2002, uses evidence‐based medicine (EBM) principles to evaluate the relative therapeutic value of new medicines and advises the Minister of Social Affairs who takes the reimbursement decisions and who can only deviate from the CRM proposal, which is taken on a two‐thirds majority, on either social or budgetary concerns [12, 13]. The reimbursement procedure has been described elsewhere in detail [14].…”
Section: Methodsmentioning
confidence: 99%
“…Minister receives recommendations, seeks advice from Minister of Budget and financial administration, and makes final decision9,17,21,62,175…”
Section: Tablementioning
confidence: 99%